Delimitation of Endangered Telmatobius Species (Anura: Telmatobiidae) of the Chilean Salt Puna - Pablo Fibla; Paola A. Sáez; Gabriel Lobos; Nicolás Rebolledo; David Véliz; Luis Pastenes; Talía del Pozo; Marco A. Méndez (Animals, 2024)
Clarifying the taxonomic status and distribution of endangered species is crucial to their conservation. In this study, we contrasted different lines of evidence (morphology, mtDNA, and nucDNA: microsatellites and SNP) to clarify the taxonomic status of endangered Telmatobius water frog species and unidentified populations that inhabit the Salt Puna in Chile. We studied population differentiation and species divergence by performing morphometric, population genetic and species delimitation analyses. The results confirmed the species status of Telmatobius fronteriensis and T. philippii, as they exhibited morphometric, mitochondrial and genomic SNP divergence. Although Bayes factor delimitation analysis indicated that the Telmatobius populations of Ascotán and Carcote could represent a new species, their few mitochondrial differences and similar morphology with respect to T. philippii suggested otherwise. Instead, they can be considered an evolutionarily significant unit of T. philippii that has differentiated from the type locality. These results extend the geographic distribution of T. philippii, which is categorized as critically endangered by the IUCN.